2009
DOI: 10.1063/1.3270520
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a supersonic laser-driven plasma jet in a cylindrical channel

Abstract: A simple method of supersonic plasma jet production where the jet is formed in a cylindrical channel guiding the plasma generated from a laser-irradiated thin foil target is proposed and examined. High-Mach number ͑Ն10͒ plasma jets of parameters relevant to laboratory astrophysics applications using 120 J, 1.315 m, and 0.3 ns laser pulse for a thin CH foil irradiation are demonstrated. The method seems to be flexible in the production of jets of various compositions and hydrodynamic parameters and does not req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Simplicity and reliability of the PALS single-beam jet generation enabled experiments ranking from laboratory astrophysics (Nicolai et al, 2009) to fusion related research (Badziak et al, 2009). Due to unusual features of the observed jets, the influence of different phenomena such as magnetic field (Nicolai et al, 2006), radiative cooling (Nicolai et al, 2006), nonlinear laser-plasma interaction (Kasperczuk et al, 2006), and the laser beam profile (Kasperczuk et al, 2009) have been considered as the primary cause of the jet formation.…”
Section: Introductionmentioning
confidence: 99%
“…Simplicity and reliability of the PALS single-beam jet generation enabled experiments ranking from laboratory astrophysics (Nicolai et al, 2009) to fusion related research (Badziak et al, 2009). Due to unusual features of the observed jets, the influence of different phenomena such as magnetic field (Nicolai et al, 2006), radiative cooling (Nicolai et al, 2006), nonlinear laser-plasma interaction (Kasperczuk et al, 2006), and the laser beam profile (Kasperczuk et al, 2009) have been considered as the primary cause of the jet formation.…”
Section: Introductionmentioning
confidence: 99%
“…6), which means that the average plasma velocity in the channel is <v> ~ (1.5 -2) ×10 7 cm/s. This velocity was found to be comparable to the velocity of a plasma jet of relatively low electron density (~10 18 -10 20 cm -3 ) observed at the channel output in the AA scheme [13]. However, contrary to the AA case, such a plasma jet was not recorded in the LICPA scheme.…”
mentioning
confidence: 69%
“…We have observed that in the case of employing LICPA without the channel, a very shallow crater or no crater was produced in the Al target placed at distances from the CH foil comparable to the channel length (1or 2mm). It indicates that in such a case the energy accumulated in the cavity is finally dispersed in a large angle like in the case of using AA for the foil acceleration in free space [13] .…”
mentioning
confidence: 99%
“…It is based on irradiation of a flat massive target with atomic number Z ≥ 29 (Z = 29 corresponds to Cu) by a single partly defocused laser beam . Also, recently, we proposed and demonstrated effective formation of a supersonic forward-emitted plasma jet by using a cylindrical channel, which guides and collimates the plasma produced from a laser-irradiated thin-foil target (Badziak et al, 2009). Recently, our investigations of the mechanisms of the plasma jet creation (Kasperczuk et al, 2009a) have shown that the geometry of target irradiation is crucial, the annular target irradiation being necessary for plasma jet formation.…”
Section: Introductionmentioning
confidence: 99%